The Relationship Between Fried Food Consumption, Alcohol Consumption, and Nutritional Knowledge of "Isi Piringku Model T" with the Incidence of Overweight in 19-44 years Adult in Indonesia - Yudhayanti, Titik; Setyaji, Diyan Yunanto (Journal of Global Nutrition, 2024)
The prevalence of overweight in Indonesia increased very quickly from 8.6% in 2007 to 11.5% in 2013, and increased to 13.6% in 2018. This research aims to determine the relationship between fried food consumption patterns and consumption patterns. alcohol, and nutritional knowledge of "Isi Piringku Model T" with the incidence of overweight at the age of 19-44 years in Indonesia. Respondents in this study numbered 581 from all over Indonesia and were aged 19-44 years. The sampling technique was non-random sampling technique with consecutive sampling method. This research uses a cross sectional research design. The data collection instrument uses a questionnaire via Google Form. Data were analyzed using descriptive statistical analysis and Chi Square test. The results showed that the type and frequency of fried food consumption, status, frequency, amount of alcohol consumption, and nutritional knowledge of "Isi Piringku Model T" showed a relationship that was not statistically significant (p>0.05). Based on the research results, it can be concluded that there is no significant relationship between consumption of fried foods, alcohol consumption, nutritional knowledge of "Isi Piringku Model T" and the incidence of overweight in adults aged 19-44 years in Indonesia.